2004
DOI: 10.1523/jneurosci.3196-04.2004
|View full text |Cite
|
Sign up to set email alerts
|

Acid-Sensing Ion Channel 2 Contributes a Major Component to Acid-Evoked Excitatory Responses in Spiral Ganglion Neurons and Plays a Role in Noise Susceptibility of Mice

Abstract: Ion channels in the degenerin-epithelial sodium channel (DEG-ENaC) family perform diverse functions, including mechanosensation. Here we explored the role of the vertebrate DEG-ENaC protein, acid-sensing ion channel 2 (ASIC2), in auditory transduction. Contributions of ASIC2 to hearing were examined by comparing hearing threshold and noise sensitivity of wild-type and ASIC2 null mice. ASIC2 null mice showed no significant hearing loss, indicating that the ASIC2 was not directly involved in the mechanotransduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0
1

Year Published

2006
2006
2010
2010

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(53 citation statements)
references
References 34 publications
2
49
0
1
Order By: Relevance
“…For the nervous systems, differences in the localization of ASIC subtypes have been reported: all ASIC subtypes were observed in the peripheral nervous system (PNS) while ASIC1a, 2a and 2b were found in the spinal cord and ASIC1a, 2a and 4 in the brain (Price et al, 1996;Chen et al, 1998;Babinski et al, 2000;Peng et al, 2004;Lingueglia, 2007). We also reported that ASIC2 expression was detected in the ciliated cells of the rat trachea although the subtypes were not clarified in our previous study (Kikuchi et al, 2008).…”
Section: Discussionmentioning
confidence: 74%
“…For the nervous systems, differences in the localization of ASIC subtypes have been reported: all ASIC subtypes were observed in the peripheral nervous system (PNS) while ASIC1a, 2a and 2b were found in the spinal cord and ASIC1a, 2a and 4 in the brain (Price et al, 1996;Chen et al, 1998;Babinski et al, 2000;Peng et al, 2004;Lingueglia, 2007). We also reported that ASIC2 expression was detected in the ciliated cells of the rat trachea although the subtypes were not clarified in our previous study (Kikuchi et al, 2008).…”
Section: Discussionmentioning
confidence: 74%
“…This K + selective leak channel passes larger outward than inward currents due to open channel rectification (Plant et al 2005). TWIK-1 (KCNK1) and TWIK-2 (KCNK6) were found previously in the rodent inner ear using RT-PCR and immunolocalized to the strial and dark cells of the cochlea and vestibule, respectively (Nicolas et al 2003;Mhatre et al 2004).…”
Section: K+ Channelsmentioning
confidence: 80%
“…TRPV1 channel not revealed by high-throughput experiments was identified previously by PCR (Kitahara et al 2005). TRPV2 was identified recently by MPSS analysis of mouse inner ear (Peters et al 2007). …”
Section: Trp Channelsmentioning
confidence: 97%
See 1 more Smart Citation
“…Details of the ABR testing protocol are given in our previous publication (23). Briefly, mice were anesthetized with ketamine (80 mg/kg) and xylazine (10 mg/kg).…”
Section: Abr and Ep Measurements For Objectively Determining Hearing mentioning
confidence: 99%